Step by step Microsoft Office Excel 2003 - Fyre, Curtis, 1968- (Microsoft Step by step)
Summary: Teach yourself how to use the data-presentation and number-crunching power in the latest version of Excel, one step at a time. Learn exactly the skills you need for Excel 2003 using easy, self-paced lessons and hands-on practice exercises.